Ground reaction forces during sprint hurdles - Nagahara, R.; Wakamiya, M.; Shinohara, Y.; Nagano, A. (Journal of Sports Sciences, 2021)
This study aimed to demonstrate ground reaction forces (GRFs) during sprint hurdles and to clarify determinants of faster sprint hurdlers. Eleven male hurdlers performed 60-m sprint hurdle trials, clearing five hurdles, during which step-to-step spatiotemporal and GRF variables were measured. The preparatory step showed smaller braking and effective vertical impulses compared with the other steps, possibly lowering the centre of mass (CM). The greater braking and smaller propulsive impulses, which result in negative net anteroposterior impulse, were characteristics of the hurdle step. This deceleration may be due to producing a large elevation of CM for clearing the hurdle through large vertical GRF production. Compared with the other steps, the second greatest braking mean force and relatively small propulsive impulse, and large propulsive impulse through long propulsive time were shown at the landing and recovery steps, respectively. The results showed better sprint hurdle performance could be achieved by minimizing braking impulse through suppressing braking time, and increasing propulsive impulse through maximizing propulsive mean force at the hurdle step; suppressing braking and propulsive times at the landing step; minimizing propulsive time, increasing effective vertical mean force, and maximizing anteroposterior net mean force through increasing propulsive mean force at the recovery step.